The role of experiential knowledge in hospital nurses' management of pain-related agitation in people with dementia: An expert performance simulation study. (March 2022) - Graham, Frederick; Fielding, Elaine; Beattie, Elizabeth
Abstract: Background: Pain-related agitation in hospital patients with dementia presents a diagnostic challenge as patients often cannot explain their agitation. Generally, a deductive process is required of staff, culminating in an analgesic trial. However, evidence suggests the deductions of hospital nurses may be flawed because they may not associate agitation in dementia with painful conditions, thereby missing key clinical cues. While analytical rule-based deduction applies explicit formal knowledge, cognitive scientists argue that tacit experiential knowledge, i.e., the unconscious classification of available cues, is equally important and is always involved. Aim: To identify the cognitive characteristics unique to nurses who accurately recognise pain-related agitation in a patient with dementia compared with nurses who do not. Methods: In this descriptive multivariate study, registered acute-care nurses undertook an original computerised virtual simulation requiring them to identify and manage pain-related agitation in a standardised patient with dementia. Process tracing methods captured nurses' simulation performances alongside their retrospective accounts of thinking. These were correlated with demographic characteristics related to seniority, workplace, training, experience and knowledge captured on a questionnaire. Dual processing theory enabled interpretation of intuitive and analytical cognitive processes. Findings: Registered medical and surgical nurses ( N = 274) participated from 10 hospitals. Although formal knowledge about pain in dementia was high (88%), only 13(4.7%) nurses identified pain-related agitation from an injury. These individuals took the longest and used the most cues, undertaking a detailed deductive search. Their recognition of pain-related cues demonstrated accurate experiential knowledge while another 16 nurses identified a fracture without linking the injury to agitation. Over three quarters (78%) of nurses decided on initial antipsychotic treatment. They were quick to decide, using the fewest cues, suggesting agitation was recognised as typical and familiar, with the solution well-known (albeit ineffective). Independent of other variables, nurses working in dementia-specific units, surgical units or with more seniority had increased odds of recognising pain, revealing the influence of workplace experience. However, most surgical and dementia-unit nurses did not recognise pain. Conclusions: Hospital nurses have difficulty recognising when agitation in a patient with dementia is caused by pain. High formal knowledge about pain in dementia may not be sufficient to enable clinical recognition of pain in patients. Instead, nurses with experience in specific workplaces or senior roles may be better equipped to recognise pain-related agitation and deploy evidence-based approaches for agitation in a patient with dementia. Overall, these results lend support to the influence of experiential knowledge on performance. Tweetable abstract: In a virtual simulation, registered nurses with high formal knowledge about pain in dementia lacked the experience required to recognise pain-related agitation in a patient with dementia